Design and Implementation of LoRa-Based Forest Fire Monitoring System - Yosi Apriani; Wiwin A. Oktaviani; Ian Mochamad Sofian (Journal of Robotics and Control (JRC), 2022)
One of the great disasters on earth is forest fires. Attempts to detect disaster events have been made with the help of monitoring technology. However, the problem is that the sensor is less responsive to detecting the presence of fire. Furthermore, sending information about fire incidents throughout the forest cannot use the existing communication platform. Therefore, we designed a forest fire monitoring system using LoRa. This technology is based on wireless which can transmit data across the forest. To detect the presence of fire, Arduino Uno is used as a microcontroller that regulates input from the AMG8833 sensor and GPS Ubox 6M. The experiment shows that the AMG8833 sensor is more sensitive in detecting the presence of fire as the catch range changes between 3 to 10 meters. In that distance range, hotspots were detected 19.25 oC to 122.5 oC when testing the sensor node is done. The monitoring system developed in this study demonstrated that sensor nodes and gateways could communicate up to 500 meters apart with a signal quality of -134 dBm. The best LoRa configuration mode for this communication capability is a Bandwidth of 250, a Code Rate of 4/5, and a Spread Factor of 10.One of the great disasters on earth is forest fires. Attempts to detect disaster events have been made with the help of monitoring technology. However, the problem is that the sensor is less responsive to detecting the presence of fire. Furthermore, sending information about fire incidents throughout the forest cannot use the existing communication platform. Therefore, we designed a forest fire monitoring system using LoRa. This technology is based on wireless which can transmit data across the forest. To detect the presence of fire, Arduino Uno is used as a microcontroller that regulates input from the AMG8833 sensor and GPS Ubox 6M. The experiment shows that the AMG8833 sensor is more sensitive in detecting the presence of fire as the catch range changes between 3 to 10 meters. In that distance range, hotspots were detected 19.25 oC to 122.5 oC when testing the sensor node is done. The monitoring system developed in this study demonstrated that sensor nodes and gateways could communicate up to 500 meters apart with a signal quality of -134 dBm. The best LoRa configuration mode for this communication capability is a Bandwidth of 250, a Code Rate of 4/5, and a Spread Factor of 10.